Analisis Penggunaan Teknologi Fiksi Ilmiah Dalam Novel Hujan Karya Tere Liye - Irene Pasca Nurahdika, Ni Putu; Al Murod, Shibghotullah; Dwi Kurniawan, Eva (Shofanah Media Berkah, 2023)
In today's daily life, technology is an element that cannot be separated from humans. Rapid developments in digital technology have had a major impact on the way we work, interact and participate in society. In this research, technology will be analyzed science fiction technology that we usually only see and read about in films, novels or so on. The aim of this research is to analyze and understand the science fiction technologies contained in the novel Rain by Tere Liye. What are the advances in technology like in the novel, how the characters in the novel respond to technological developments and how technology influences the story narrative in the novel. In the novel used entitled Rain by Tere Liye, data about technology which has elements of science fiction is found from direct descriptions or dialogue between characters in the novel. The research method used in this novel is a hermeneutic approach. In this novel there are 4 elements of important discoveries related to science fiction technology in the form of memory modification machines, medical robots, chip devices, and hologram screens.